Meningkatkan Komunikasi Proses Belajar Mengajar Melalui Diskusi Tanya Jawab Dalam Membentuk Karakter Siswa Di SMP Negeri 18 Medan - Haratua Aritonang (JOURNAL SAINS STUDENT RESEARCH, 2023)
Communication is needed by almost all human activities, wherever they are, they are always touched by communication. Education cannot run without the support of communication, even education can only work through communication. "In other words, there is no educational behavior that is not born by communication. How is it possible to educate people without communicating, teaching people without communicating or giving lectures without speaking. Everything needs communication.” 1 Without communicating human life will not run as a whole and will experience a problem, this is because human communication is not carried out properly. In the research that I am currently doing, I am conducting research at SMP Negeri 18 Medan. In this case I observed the behavior of every school member in Medan 18 Public Middle School, and to make it easier I took a sample of class IX students, every day I observed the way they communicated between friends, between students and teachers, and between students and students. other staff members. And I also conducted a question and answer discussion with class IX students with what subject matter each student liked the most and out of 11 subjects, almost 80% of both students liked sports subjects, and 20% others liked other subjects. And also I asked what subjects they disliked the most and out of 100% of class IX students 50% did not like Social Sciences subjects, the other 50% did not like Mathematics. And when carrying out the question and answer discussion, I also saw the way each student communicated, and I can conclude that each student has a unique personality when communicating with me. There were students who answered impressively as if they were used to being asked questions by other people, and there were also students who answered with embarrassment, maybe because these students were a little closed to their surroundings. And this is my biggest motivation in raising the title of this research, and I hope that through this research students at SMP Negeri 18.[1]With the new learning system, you can build a fun teaching and learning atmosphere. I tried to form one of the systems while making observations at SMP Negeri 18 Medan. I try to apply the question and answer discussion before the lesson begins. This plays an important role in shaping the attitude and character of a student when participating in education. Every student will have good self-confidence when they can understand lessons at school and of course they will be even more active for future lessons. This is one of the efforts to advance education in Indonesia in order to educate the life of the nation and state.